Georgia Librarians Working from Home during the COVID-19 Pandemic - Bennett, Stephanie; Hines Chriszt, Maxine; Cole, Jolene; Day, Marie; Dickson, Chelsee; Doster-Greenleaf, Karen; Evans, Rachel S; Foster, Susan; Glover, Sarah Grace; Greene, Kristy; Harris, Karen J; Jordan, Austina; et al. (The Georgia library quarterly, 2020)
In Mid-March of 2020, libraries across the United States began closing in response to the COVID-19 Pandemic, sending employees home. To document this period in time, Georgia library employees contributed short essays on their experiences with working from home, including how they continued to provide library services and resources to their users.